2018
DOI: 10.1002/lary.27471
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold botulinum toxin injection for refractory paradoxical vocal fold motion disorder

Abstract: Objective Demonstrate efficacy of vocal fold botulinum toxin injection for treatment of refractory paradoxical vocal fold motion disorder (PVFMD). Methods A retrospective review was completed of patients diagnosed with PVFMD who underwent vocal fold botulinum toxin injection for dyspnea symptoms that persisted despite laryngeal control therapy, medical management, and biofeedback therapy. Outcomes measured included overall improvement and resolution of dyspnea symptoms, number of botulinum toxin injections and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
(83 reference statements)
0
10
0
1
Order By: Relevance
“…Improvement in VCD symptoms following the intervention was reported in three of the four studies. A reduction in dyspnoea symptoms was reported by de Silva et al 38 using the Dyspnea Index. 37 Baxter et al 38 reported participants in their study required an average of 3.85 injections ranging from 1 to 12 when followed for an average of 24 months.…”
Section: Botulinum Toxin Injectionsmentioning
confidence: 71%
See 4 more Smart Citations
“…Improvement in VCD symptoms following the intervention was reported in three of the four studies. A reduction in dyspnoea symptoms was reported by de Silva et al 38 using the Dyspnea Index. 37 Baxter et al 38 reported participants in their study required an average of 3.85 injections ranging from 1 to 12 when followed for an average of 24 months.…”
Section: Botulinum Toxin Injectionsmentioning
confidence: 71%
“…7,38,41 This was evident in studies investigating the use of botulinum toxin injections where participants reported ongoing VCD symptoms following glottic airway and respiratory retraining. 7,33,38,41 The number of sessions attended was described as at least two 41 or when the participants had exhausted laryngeal control techniques. 38 Adherence to techniques was not reported.…”
Section: Treatment Resultsmentioning
confidence: 98%
See 3 more Smart Citations